A Mexican Autodefensa Facebook Group's use of binarity, legitimization strategies, and topoi of religion, family and struggle. (August 2021) - Sierra, Sylvia
Abstract: In recent years, Critical Discourse Analysis (CDA) has expanded from its earlier focus on right-wing discourse to also examining discourses of resistance in grassroots political movements around the world. At the same time, CDA has begun to explore the role of social media in these alternative discourses. In this study, I combine a CDA framework with a social media focus to investigate the online discourse of the Mexican Autodefensa (self-defense) movement (2013 to present), an armed grassroots movement formed by citizens to fight against drug cartel control. I analyze one Autodefensa's Facebook page discourse, showing how their collective identity and ideology emerge in opposition to a cartel via the construction of binarity, which is developed through their increasingly explicit nomination and predication of themselves and the cartel. Also crucial to this ideology and identity construction is the use of topoi (argumentative shortcuts) regarding religion, family, and struggle, along with legitimization strategies of rationalization, altruism, reference to a hypothetical future, and appeal to emotions. This CDA study shows how an Autodefensa discursively constructs collective identity and ideology on Facebook as a righteous family-like unit with religious backing united in struggle to save their region from unjust cartel control.